Description of the conceptual-architectural model of the smart city - Togzhanova, K. O.; Rametov, N. (Харківський національний автомобільно-дорожній універститет, 2024)
Today, cities have become the main drivers of economic development, standing at the forefront of production and consumption networks. They shape social and economic relations and contribute a significant portion of the gross domestic product (GDP) in many countries. Cities play a central role in national, regional, and global development, and the quality of life for people depends on them. As a result, there are growing demands on cities that were unprecedented in the past, including the need for accessible urban infrastructure, high mobility, urban security, environmental cleanliness, and the development of local self-government.
Keywords: Information and Communication Technologies; smart city